miR-590-3p Promotes Ovarian Cancer Growth and Metastasis via a Novel FOXA2-Versican Pathway - Salem, Mohamed; O'Brien, Jacob A; Bernaudo, Stefanie; Shawer, Heba; Ye, Gang; Brkić, Jelena; Amleh, Asma; Vanderhyden, Barbara C; Refky, Basel; Yang, Burton B; Krylov, Sergey N; Peng, Chun (Cancer research (Chicago, Ill.), 2018)
miRNAs play important roles in gene regulation, and their dysregulation is associated with many diseases, including epithelial ovarian cancer (EOC). In this study, we determined the expression and function of miR-590-3p in EOC. miR-590-3p levels were higher in high-grade carcinoma when compared with low-grade or tumors with low malignant potential. Interestingly, plasma levels of miR-590-3p were significantly higher in patients with EOC than in subjects with benign gynecologic disorders. Transient transfection of miR-590-3p mimics or stable transfection of mir-590 increased cell proliferation, migration, and invasion. studies revealed that mir-590 accelerated tumor growth and metastasis. Using a cDNA microarray, we identified forkhead box A2 (FOXA2) and versican (VCAN) as top downregulated and upregulated genes by mir-590, respectively. miR-590-3p targeted FOXA2 3' UTR to suppress its expression. In addition, knockdown or knockout of FOXA2 enhanced cell proliferation, migration, and invasion. Overexpression of FOXA2 decreased, whereas knockout of FOXA2 increased VCAN mRNA and protein levels, which was due to direct binding and regulation of the VCAN gene by FOXA2. Interrogation of the TCGA ovarian cancer database revealed a negative relationship between FOXA2 and VCAN mRNA levels in EOC tumors, and high FOXA2/low VCAN mRNA levels in tumors positively correlated with patient survival. Finally, overexpression of FOXA2 or silencing of VCAN reversed the effects of mir-590. These findings demonstrate that miR-590-3p promotes EOC development via a novel FOXA2-VCAN pathway. Low FOXA2/high VCAN levels mediate the tumor-promoting effects of miR-590-3p and negatively correlate with ovarian cancer survival. .